Thallium Induced Sub-chronic Toxicity Profile in Wistar Rats - Sindhi, Parvez I.; Raval, Samir H.; Singh, Ratn Deep; Parmar, Rohit S.; Patel, Jasmi G.; Patel, Bakor J.; Joshi, Dilip V. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Thallium (Tl) is one of the most toxic heavy metals affecting both humans and animals, yet is one of the least studied for its toxicological effects. A total of 40 male Wistar rats were randomly divided into four Groups with 10 rats in each  Group. Group I received distilled water only and served as a control. Group II, III, and IV received thallium sulfate (I) at 0.48, 0.93, and 1.33 mg/kg body weight, respectively, in drinking water for 90 days. In Group IV rats, lethargy, dehydration, weakness, mild diarrhea, weight loss and 100% morality in male Wistar rat were noted. Group II and III rats showed significant reduction in cholesterol, phosphorus, triglyceride level, and absolute and relative spleen weight. Microscopically, thallium sulfate (I) found to cause lymphoid depletion in white pulp of spleen in all treatment Groups. In kidney of Group IV rats, tubular necrosis, cytoplasmic vacuolation or clearing of tubules, cast, and thrombosis were found. Dose dependent hyperkeratosis was found in non-glandular stomach in all three treated Groups. In conclusion, spleen, kidney and stomach were primarily affected organs in sub-chronic thallium toxicity.
Keywords: Repeated 90 days study; Sub-chronic toxicity; Thallium sulfate (I); Wistar rats